Therapeutic strategy in the form of communication in the children with the autism spectrum disorders - narrative review - Dominika Nowak; Magdalena Próchnicka; Michał Siwek; Adrian Giermasiński; Weronika Tuszyńska; Adam Zarzycki; Mateusz Komisarczuk (Kazimierz Wielki University, 2023)
Autism spectrum disorders (ASD) is a neurodevelopmental disorder influenced by a number of genetic and environmental factors. It is characterized by a broad range of symptoms, particularly in the areas of communication and language, which pose a therapeutic challenge for both parents and therapists.   This article, based on a review of available studies on PubMed, presents therapeutic methods based on functional communication strategies and ways to implement them as a form of treatment for children with the autism spectrum disorders.   The major goals of ASD treatment are socialization and communication skills improvement and current treatments are not based on pharmacological therapies, but on behavioral therapies. Through appropriate speech development and practical communication strategies that are based on techniques like motivating the child to create eye contact with an adult, it is possible to realize the development of proper communication. These strategies are a form of therapy and allow for the improvement of the child's communication on multiple levels and shaping the social attitudes. Incorporating suitable therapeutic communication techniques enables the development and enhancement of social skills in children with autism spectrum disorders. Children with ASD benefit from appropriate communication because it helps them communicate their needs, understand the social norms, and improve their quality of life.